Creating alternative seafood flavour from non-animal ingredients: A review of key flavour molecules relevant to seafood - Luo, J; Frank, D; Arcot, J (Food Chemistry: X, 2024)
This review summarises current knowledge of the molecular basis for flavour profiles of popular seafood types (crustacean (crab, lobster, prawn, etc.), mollusc (oyster, squid, etc.), oily fish (salmon, sardine, etc.) and white fish (barramundi, turbot, etc.)), and provides a foundation for formulating improved plant-based seafood alternative (PBSA) flavours. Key odour-active volatile molecules were identified from a systematic review of published olfactometry studies and taste-active compounds and macronutrient profiles of different seafood species and commercial PBSAs from nutrition databases were compared. Ingredients commonly used in commercial BPSAs and new potential sources of flavouring agents are evaluated. While significant challenges in replicating seafood flavour and texture remain, this review provides some insights into how plant-based ingredients could be applied to improve the acceptability of PBSAs.